Exploring new paths towards biological anion recognition by lanthanide complexes - Alexander, C (2022)
Anions are ubiquitous in nature. In order to understand them in their natural setting, this thesis focusses on developing lanthanide complexes as hosts for the recognition of biologically relevant anions, particularly chloride and sialic acid. Chapter-I introduces lanthanide chemistry encompassing macrocyclic complexes, luminescence, and MRI. An account of anion recognition and lanthanide complexes used as hosts for biologically relevant anions are reviewed.